2015
DOI: 10.1002/ptr.5305
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Effects of the Extracts of Cordyceps militaris via Erk Phosphorylation in a Renal Cell Carcinoma Cell Line

Abstract: Cordyceps militaris (CM) is gaining attention as a traditional medicinal food, but its molecular biological mechanisms for anti-cancer activity are not identified or clarified. We aimed to elucidate the synthesizing apoptotic effects of CM extracts and to determine the biological effects of CM extract against cordycepin alone in a renal cell carcinoma (RCC) cell line. CM extract showed higher effects of growth inhibition, apoptotic effect, and cell cycle arrest than cordycepin alone. Moreover, CM extract activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…tential therapeutic effects of cordycepin in renal cell carcinoma (20,48). Researchers found that cordycepin could induce cell apoptosis in renal cell carcinoma via ERK-JNK signaling pathways (20,48). Consistent with these reports, results from present study confirmed the apoptotic effects of cordycepin in Caki-1 cells, one of renal cell carcinoma cell lines.…”
Section: Effects Of Cordycepin On Renal Cell Carcinoma Caki-1 Cellssupporting
confidence: 87%
See 2 more Smart Citations
“…tential therapeutic effects of cordycepin in renal cell carcinoma (20,48). Researchers found that cordycepin could induce cell apoptosis in renal cell carcinoma via ERK-JNK signaling pathways (20,48). Consistent with these reports, results from present study confirmed the apoptotic effects of cordycepin in Caki-1 cells, one of renal cell carcinoma cell lines.…”
Section: Effects Of Cordycepin On Renal Cell Carcinoma Caki-1 Cellssupporting
confidence: 87%
“…2A and 2B, 10 μg/mL cordycepin treatment significantly suppressed cell migration of Caki-1 cells at both 24 h and 48 h incubation. tential therapeutic effects of cordycepin in renal cell carcinoma (20,48). Researchers found that cordycepin could induce cell apoptosis in renal cell carcinoma via ERK-JNK signaling pathways (20,48).…”
Section: Effects Of Cordycepin On Renal Cell Carcinoma Caki-1 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…COR was previously reported to have anti-tumor ( 29 , 30 ), anti-inflammatory ( 31 ) and anti-oxidant ( 32 ) activities. However, the potential role and mechanisms of COR in the treatment of AMoL have remained to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In general, those drugs often anti-metabolites that interfere with nucleic acid or protein synthesis can suppress the immune response. The greatest problem facing the physician is to effectively balance at the same time the dosages of drugs or irradiation so that the immune system is suppressed against the graft, but is still capable of defense against environmental pathogens [32][33][34][35][36][37][38][39][40][41][42].…”
Section: Acquired Immuno-suppressionmentioning
confidence: 99%